Revision of the genus Synelmis Chamberlin, 1919 (Annelida: Phyllodocida: Pilargidae) in Australia - Glasby, Christopher J.; Marks, Shona (Zootaxa, 2013)
We provide accounts of four species of Synelmis Chamberlin, 1919 (Annelida: Phyllodocida: Pilargidae) from Australian and adjacent seas, including one new species, S. sergi sp. nov. The only previous, positively identified, record of a Syn-elmis species in the region, S. gibbsi Salazar-Vallejo, 2003, has been checked and the specimens re-identified here as S. knoxi Glasby, 2003, which extends the known range of this species to include Australia as well as New Zealand. Newly collected material of S. gibbsi is described from the Joseph Bonaparte Gulf, NW Australia. Specimens collected from NE Australia are identified here as S. rigida (Fauvel, 1919). Synelmis knoxi, S. gibbsi and S. rigida are all new records for Australia. A key to Australian species of Synelmis is provided and we tabulate information on the distinguishing features of all 17 species in the genus.